Determining soil organic carbon concentration in agricultural fields using a handheld spectroradiometer: Implication for soil fertility measurement - Tola, ElKamil; Al-Gaadi, Khalid A.; Madugundu, Rangaswamy; Kayad, Ahmed G.; Alameen, Ahmed A.; Edrees, Haroon F.; Edrris, Mohamed K. (International Journal of Agricultural and Biological Engineering, 2018)
The soil organic carbon (SOC) plays a vital role in plant growth and development, and therefore is considered as one of the most important indicators of soil quality. This study was carried out in the central region of Saudi Arabia to explore the potential of spectroscopy in determining the SOC concentration in low-fertility soils. Spectral reflectance data were collected, under the controlled laboratory conditions on 39 air-dried 2.0 mm sieved soil samples, using a handheld spectroradiometer of a wavelength range between 350 nm and 2500 nm in the direct contact probe mode. The concentration of the SOC was determined using the Walkley and Black (W&B) and the UV-VIS spectrophotometric methods. The increase in the concentration of SOC was associated with a decrease in the corresponding spectral reflectance. Regression analysis showed linear relationships with high significant correlation between the spectral reflectance and the SOC measured by both the UV-VIS (Model-1: R2=0.46, p=0.00015 and RMSE=6.6 g/kg) and the W&B (Model-2: R2=0.48, p=8.92E-05 and RMSE= 2.8 g/kg) methods. For these models, two wavebands with wavelengths of 2167 nm (Model-1) and 1359 nm (Model-2) were identified as the most sensitive bands to the SOC concentration. The cross-validation confirmed the validity of Model-1 with R2, p and RMSE values of 0.50, 0.0099 and 6.6 g/kg, respectively. The validation results of the Model-2 showed values of R2, p and RMSE of 0.72, 0.00023 and 4.0 g/kg, respectively. Results of this study revealed the possibility and the potential of using the spectral reflectance technique in predicting the concentration of SOC. Keywords: soil fertility, organic carbon, modeling, spectroscopy, reflectance DOI: 10.25165/j.ijabe.20181106.4061 Citation: Tola E, Al-Gaadi K A, Madugundu R, Kayad A G, Alameen A A, Edrees H F, et al. Determining soil organic carbon concentration in agricultural fields using a handheld spectroradiometer: Implication for soil fertility measurement. Int J Agric & Biol Eng, 2018; 11(6): 13–19.